O-010 Robotic-assisted intracranial aneurysm treatment: one year follow-up imaging and clinical outcomes. (23rd July 2022) - Cancelliere, N; Lynch, J; Drake, K; Turner, R; Nicholson, P; Marotta, T; Spears, J; Liu, E; Mendes Pereira, V
Abstract : Background: Robotic-assisted neurovascular intervention has been described and we performed a world first series of six patients that just completed long-term follow up. Purpose: We aim to describe one year follow-up imaging and clinical results from our case series of robotic-assisted intracranial aneurysm repairs. Results: To date, we have performed more than 35 robotic-assisted intracranial aneurysm embolizations using a neuroendovascular approach. The one-year results of six patients are presented. Four patients were treated with a neck-bridging stent (± coiling) and two patients were treated with a flow-diverting stent. Two patients were treated in the subacute period of subarachnoid haemorrhage and 4 patients were treated electively. All clinical procedures were technically successful, with all intracranial steps being performed robotically with no conversions to manual intervention or failures of the robotic system. The technical success rate of the procedures was 100%. There was no morbidity or mortality associated with the procedures. One year follow-up imaging showed that 4 aneurysms were completely obliterated (RROC class I) and the remaining 2 were occluded with a residual neck (RROC class II). Conclusions: Robotic neuro-procedures were safely and effectively performed. Our one-year results demonstrate stable occlusion results in the midterm follow-up. Disclosures: N. Cancelliere: 2; C; Corindus. J. Lynch: None. K. Drake: 5; C; Corindus. R. Turner: 5; C; Corindus. P. Nicholson: None. T. Marotta: None. J. Spears: None. E. Liu: None. V. Mendes Pereira: 2; C; Corindus.